Lust for Life : The Story of Vincent Van Gogh - Stone, Irving (London Magnum Books, 1980)
The most famous of all of Stone$1 (Bs novels, it is the story of Vincent Van Gogh$1 (Bbrilliant painter, passionate lover, and alleged madman. Here is his tempestuous story: his dramatic life, his fevered loves for both the highest-born women and the lowest prostitutes, and his paintings$1 (Bfor which he was damned before being proclaimed a genius. The novel takes us from his desperate days in a coal mine in southern Belgium to his dazzling years in the south of France, where he knew the most brilliant artists (and the most depraved whores). Finally, it shows us Van Gogh driven mad, tragic, and triumphant at once. No other novel of a great man$1 (Bs life has so fascinated the American public for generations.s
Keywords: Gogh, Vincent van, -- 1853-1890 -- Fiction -- Painters -- Fiction